2012
DOI: 10.1111/j.1528-1167.2012.03669.x
|View full text |Cite
|
Sign up to set email alerts
|

A guinea pig model of mesial temporal lobe epilepsy following nonconvulsive status epilepticus induced by unilateral intrahippocampal injection of kainic acid

Abstract: SUMMARYPurpose: Models of temporal lobe epilepsy are commonly utilized to study focal epileptogenesis and ictogenesis. The criteria that define animal models representative of human mesial temporal lobe may vary in different laboratories. We describe herein a focal epilepsy model of mesial temporal (hippocampal) origin that relies on the analysis of interictal and ictal electroencephalography (EEG) patterns and on their correlation with seizure symptoms and neuropathologic findings. The study is based on guine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 52 publications
6
54
1
Order By: Relevance
“…Intracranial multichannel EEG signal analysis demonstrated that a parameter of synchronization (eigenvalue) is reduced during the early phases of a seizure and progressively augments when seizure end approaches. 5,32 These findings are consistent with the observation of irregular and asynchronous activity patterns during the early seconds of seizures recorded in vivo in animal models of epilepsy 14,[33][34][35] and during acute seizures on in vitro preparations. 8,10,36 Experimental studies performed on cortical and hippocampal slices maintained in vitro also suggest that seizures are initiated by a reduction of neuronal synchrony.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Intracranial multichannel EEG signal analysis demonstrated that a parameter of synchronization (eigenvalue) is reduced during the early phases of a seizure and progressively augments when seizure end approaches. 5,32 These findings are consistent with the observation of irregular and asynchronous activity patterns during the early seconds of seizures recorded in vivo in animal models of epilepsy 14,[33][34][35] and during acute seizures on in vitro preparations. 8,10,36 Experimental studies performed on cortical and hippocampal slices maintained in vitro also suggest that seizures are initiated by a reduction of neuronal synchrony.…”
Section: Discussionsupporting
confidence: 91%
“…Brief applications of either the c-aminobutyric acid (GABA) A receptor blocker, bicuculline methiodide (BMI), or the potassium channel blocker, 4-aminopyridine (4AP), induced in the hippocampus and in the parahippocampal region a typical focal seizure pattern that initiates with low-voltage fast activity, followed by irregular spiking activity; the late phase of the ictal discharge is characterized by large-amplitude, synchronous bursts that recur periodically [6][7][8][9][10] and show widespread propagation. 11 A similar sequence of events was observed during seizures recorded in the limbic cortex of animal models of temporal lobe epilepsy developed in rats, 12 mice, 13 and guinea pigs 14 and in human seizures recorded with intracerebral electrodes during presurgical monitoring studies in patients with pharmacoresistant focal epilepsies. [15][16][17][18][19] We explore here the possibility that enhancement of excitation during the late periodic ictal bursting induces a progressive enhancement of inhibition (depression) that brings seizures to end.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…These models usually show remarkable similarity to human hippocampal pathology in TLE (Sloviter, 1996; Bernard et al, 1998; Ben-Ari, 2001; Sharma et al, 2007; Curia et al, 2008; Tang and Loke, 2010; Carriero et al, 2012), including sclerosis, loss of pyramidal cells in the CA1 and CA3c regions, hilar interneuronal loss, and the preservation of calbindin-containing interneurons (Sloviter et al, 1991; Wittner et al, 2002). …”
Section: Epilepsy Models and The Fate Of Cr-containing Interneuronsmentioning
confidence: 99%
“…Advantages and disadvantages of the in vitro IWB in comparison to other in vitro models and to the in vivo condition are summarized in Table 1. As future advancement, we plan to isolate brains from chronically epileptic guinea pigs (Arcieri et al, 2014;Carriero et al, 2012) to study network changes induced by the epileptogenic process.…”
Section: Discussionmentioning
confidence: 99%